New mobilizable vectors suitable for gene replacement in gram-negative bacteria and their use in mapping of the 3' end of the Xanthomonas campestris pv. campestris gum operon - Katzen, F. (1999)
We describe useful vectors to select double-crossover events directly in site-directed marker exchange mutagenesis in gram-negative bacteria. These vectors contain the gusA marker gene, providing colorimetric screens to identify bacteria harboring those sequences. The applicability of these vectors was shown by mapping the 3' end of the Xanthomonas campestris gum operon, involved in biosynthesis of xanthan.